A qualitative evaluation of a brief multicomponent intervention provided by lay health workers for women affected by adversity in urban Kenya. (6th February 2018) - van't Hof, Edith; Dawson, Katie S.; Schafer, Alison; Chiumento, Anna; Harper Shehadeh, Melissa; Sijbrandij, Marit; Bryant, Richard A.; Anjuri, Dorothy; Koyiet, Phiona; Ndogoni, Lincoln; Ulate, Jeannette; van Ommeren, Mark
Abstract : Background: Problem Management Plus (PM+) is a brief multicomponent intervention incorporating behavioral strategies delivered by lay health workers. The effectiveness of PM+ has been evaluated in randomized controlled trials in Kenya and Pakistan. When developing interventions for large-scale implementation it is considered essential to evaluate their feasibility and acceptability in addition to their efficacy. This paper discusses a qualitative evaluation of PM+ for women affected by adversity in Kenya. Methods: Qualitative interviews were conducted with 27 key informants from peri-urban Nairobi, Kenya, where PM+ was tested. Interview participants included six women who completed PM+, six community health volunteers (CHVs) who delivered the intervention, seven people with local decision making power, and eight project staff involved in the PM+ trial. Results: Key informants generally noted positive experiences with PM+. Participants and CHVs reported the positive impact PM+ had made on their lives. Nonetheless, potential structural and psychological barriers to scale up were identified. The sustainability of CHVs as unsalaried, volunteer providers was mentioned by most interviewees as the main barrier to scaling up the intervention. Conclusions: The findings across diverse stakeholders show that PM+ is largely acceptable in this Kenyan setting. The results indicated that when further implemented, PM+ could be of great value to people in communities exposed to adversities such as interpersonal violence and chronic poverty. Barriers to large-scale implementation were identified, of which the sustainability of the non-specialist health workforce was the most important one.